2006
DOI: 10.5547/issn0195-6574-ej-vol27-no3-4
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of International Oil Companies

Abstract: According to economic theory, exploration and development of new oil and gas fields should respond positively to increasing petroleum prices. But since the late 1990s, stock market analysts have focused strongly on short-term accounting return measures, like RoACE 1 , for benchmarking and valuation of international oil and gas companies. Consequently, exaggerated capital discipline among oil and gas companies may have reduced their willingness to invest for future reserves and production growth. Based on panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 16 publications
0
17
1
7
Order By: Relevance
“…Hence, the negative coefficients on oil and gas reserves may be an effect of size. Osmundsen et al (2006) found that size is positively correlated to market value in integrated oil companies. * = significant at the 10% significance level, ** = significant at the 5% significance level, *** = significant at the 1% significance level, tvalues in parenthesis.…”
Section: Part I Effects Of Accounting Methods Choicementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the negative coefficients on oil and gas reserves may be an effect of size. Osmundsen et al (2006) found that size is positively correlated to market value in integrated oil companies. * = significant at the 10% significance level, ** = significant at the 5% significance level, *** = significant at the 1% significance level, tvalues in parenthesis.…”
Section: Part I Effects Of Accounting Methods Choicementioning
confidence: 99%
“…Few academic studies have been carried out on valuation of integrated international oil companies, and they do not address accounting information (e.g. Osmundsen et al, 2006;2007). Our sample of international integrated and upstream companies allows us to compare the value relevance of these two types of companies.…”
Section: Introductionmentioning
confidence: 99%
“…Their result confirmed that a structural break took place in the valuation of oil and gas companies in the late 1990s. Additionally, Osmundsen et al (2006) found that the major determinants of firm valuation are oil price, oil and gas production, and to a certain extent, reserve replacement. To examine the relationship between stock prices returns and financial risk factors of oil companies, Giovannini et al (2006) used multivariate cointegration techniques and multivariate GARCH Model.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…ROCE is often considered as the most important performance indicator by oil and gas companies. The study by Osmundsen et al (2006) based on a panel data of 14 international oil and gas companies, finds that the variation in company valuations are explained by the oil price, oil and gas production and to a certain extent reserve replacement. Oil and gas analysts often plot key performance indicators among the companies against their respective market-based valuation multiples.…”
Section: Review Of Literaturementioning
confidence: 99%